Everyday business storytelling create, simplify, and adapt a visual narrtive for any audience - Kurnoff, Janine; Lazarus, Lee (Wiley, 2021)
"Everyday Business Storytelling: Create, Simplify, and Adapt A Visual Narrative for Any Audience (Master Presentations, One-Pagers, Emails, and Virtual Meetings) We've all been there: We work tirelessly on a crucial presentation, email or update. We've got just ONE shot to be credible, authentic and influence business decisions. But we're busy! So we leverage content within our reach--facts, data, charts, slides--hoping that an avalanche of information will make us look and sound well-prepared. But the truth is, it doesn't. It only frustrates decision-makers, requiring them to work hard to understand what they need to know and do with the information. Everyday Business Storytelling prevents the "information firehose" with one simple story framework that can be applied to any business communication. This framework helps you choreograph your ideas, data, and insights so it's easy for your audience to quickly grasp your message and take action. Grounded in theory but smothered in practicality, this book shows you real-world, everyday business stories--from the most high-stakes proposals to the "un-sexy" project updates. Another bonus? Everyday Business Storytelling is filled with clever visual techniques to humanize your story, make it memorable, and drive decision-making"